2020
DOI: 10.1136/bmjspcare-2020-002269
|View full text |Cite
|
Sign up to set email alerts
|

Complementary medicine visits by palliative care patients: a cross-sectional survey

Abstract: BackgroundThe paucity of empirical research examining complementary medicine (CM) use in palliative care in France compared with other countries results in a gap in scientific knowledge. This study aims to describe the frequency and the cause of palliative care patients consulting with a CM clinician along with the conventional physicians.MethodsThis study is an observational cross-sectional survey conducted in three palliative care centres in Lyon, France, between July 2017 and May 2018: two tertiary hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In France, a country with many economic and cultural affinities with Italy, an observational cross-sectional survey conducted in inpatients and outpatients visiting the palliative care clinics, the majority of advanced cancer patients (90%) had used CAM in the previous six months or since their primary cancer diagnosis [ 16 ]. The average out-of-pocket expenses associated with CAM use were about 157 euros/month.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In France, a country with many economic and cultural affinities with Italy, an observational cross-sectional survey conducted in inpatients and outpatients visiting the palliative care clinics, the majority of advanced cancer patients (90%) had used CAM in the previous six months or since their primary cancer diagnosis [ 16 ]. The average out-of-pocket expenses associated with CAM use were about 157 euros/month.…”
Section: Discussionmentioning
confidence: 99%
“…Information about the use of CAM in advanced cancer patients is lacking, particularly in Western European countries. A recent survey performed in France showed that a large number of advanced cancer patients (90%) were using CAM in the previous six months or since their primary cancer diagnosis [ 16 ]. This is a very impressive data, considering the Health Care system, that is similar to that of Italy.…”
Section: Introductionmentioning
confidence: 99%